Behaviour of Concrete Filled Steel Tubes (Journal of Informatics and Mathematical Sciences, 2018)
Concrete filled steel tubular columns are preferred due to their excellent static and dynamic resistant properties such as high strength, high ductility and large energy absorption capacity. The comparison of the ultimate strength of CFST with Hollow steel tube, RCC and the bond strength between concrete and the steel was done both experimentally and analytically using ANSYS. A total of 18 specimens were cast, out of which ultimate strength was determined for 13 specimens and bond strength was observed for 5 specimens using push out test. Both experimental and analytical observations using ANSYS were carried on a cylinder of height 460mm and a diameter of 113mm. The grade of concrete used for infill is M30. The tests were carried on an Ultimate Testing Machine. The ultimate strength of CFST, RCC and HST were compared and CFST having the advantages of both concrete and steel is found to behave better and average bond strength ranges between 0.7 to 1.1N/mm\(^2\).
Keywords: CFST; Load-strain; Push out test; ANSYS